2012
DOI: 10.1002/bem.21737
|View full text |Cite
|
Sign up to set email alerts
|

Between‐country comparison of whole‐body SAR from personal exposure data in Urban areas

Abstract: In five countries (Belgium, Switzerland, Slovenia, Hungary, and the Netherlands), personal radio frequency electromagnetic field measurements were performed in different microenvironments such as homes, public transports, or outdoors using the same exposure meters. From the mean personal field exposure levels (excluding mobile phone exposure), whole-body absorption values in a 1-year-old child and adult male model were calculated using a statistical multipath exposure method and compared for the five countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Finally, we performed measurements of the average electric field strength in order to provide field exposure maps, not the specific absorption rate. However, actual absorption can be determined from field exposure using the data from Neubauer et al [2010] and Joseph et al [2010b, 2012b]. This will also be part of future research.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we performed measurements of the average electric field strength in order to provide field exposure maps, not the specific absorption rate. However, actual absorption can be determined from field exposure using the data from Neubauer et al [2010] and Joseph et al [2010b, 2012b]. This will also be part of future research.…”
Section: Discussionmentioning
confidence: 99%
“…Scientists are trying to answer all calls for specific categories’ interaction with environmental or professional RF exposure. Geographical location [90,94,95], occupational groups [96,97], sections of the population [98] such as children and youngsters [99,100] or pregnant women [101] are only several elements that have been investigated in a cohort of voluntary subjects participating in research or clinical studies, or considered in informative epidemiologic meta-analysis [102] surveys. Moreover, the impacts of diagnostic devices such as magnetic resonance scanners that emit RF were analyzed [103].…”
Section: The Effects Of Rf Exposure On Humansmentioning
confidence: 99%
“…Downlink exposure will be expressed as a function of the electric-field strength generated by the incident waves from the base station (macrocell, femtocell, or AP). Most measurement campaigns verify compliance with ICNIRP electricfield reference levels, e.g., [3][4][5][6][7][8]. Also, national and international authorities (e.g., Belgium, Switzerland,...) base their regulations on electric-field levels.…”
Section: Simulation Method: Electric-field and Sar Modelsmentioning
confidence: 97%
“…Also on a national level, authorities have implemented laws and norms to limit the exposure to electromagnetic fields. A lot of research has been done on the characterization of RF exposure (e.g., [3][4][5][6][7]), and measurements have indicated that exposure in indoor environments cannot be neglected [8]. Most exposure studies merely focus on fields generated due to traffic from base station to user device (downlink), but in reality also the localized Specific Absorption Rate (SAR) due to the electromagnetic waves induced (e.g., in the user's head) by the user device should be considered (uplink).…”
Section: Introductionmentioning
confidence: 99%